A Comparative Study of Chinese and Thai Multi-Category Words Phenomena - Laocharoen, Atittaya (Journal of Sinology (วารสารจีนวิทยา), 2016)
Among various kinds of languages, word class is the classification of words in grammar, and the amount of it differs from one language to another. In “The Royal Institute Dictionary (2011 Edition),” the parts of speech of the Thai language are divided into eight word classes: nouns, pronouns, verbs, adverbs, prepositions, conjunctions, interjections, and modal particles. This research is based on the standard division of polysemy words by Liu Kai’s “Analysis on Characters with Different Parts of Speeches in Contemporary Chinese Language” for the Thai multicategory word phenomenon analysis process.